Identifikasi Potensi Pariwisata Pracimantoro: Dari Geopark Hingga Kebudayaan Daerah - Adira Damai Reforma; Ofita Purwani; Tri Yuni Iswati (Universitas Sebelas Maret Surakarta, 2020)
This paper focuses on identifying tourism potentials of kecamatan Pracimantoro, Wonogiri. This area has not been recognized as tourist destination despite the fact that some part of the area has been acknowledged as UNESCO’s Geopark. While UNESCO encourages the geopark to contribute to the economy of local people, this opportunity has not been realized fully by the people of Pracimantoro. Our research aims to identify Pracimantoro’s potentials for tourism so that the result can be used for tourism planning. By compiling potentials found in each village of Pracimantoro, and putting them into categories, we conclude that there are two main potentials for tourism in kecamatan Pracimantoro: Geopark and culture.